The United States, Japan, and Asia - Curtis, Gerald L.; Aho, C. Michael 1949- (W.W. Norton, 1994)
The robust growth of Asian economies and the end of the Cold War have radically changed the economic and security relationships that have bound the United States and Japan since the end of World War II. The Japanese are building a dominant position in the Asia Pacific economy, while the United States is reducing its military presence and asking whether it can compete with Japan economically in the region. China's growing economic and military strength adds new challenges for both countries. What should the new U.S. policy in Asia be? What role will Japan take in regional security? Can the two countries' economic relations in the region be mutually beneficial, or will Japan's reduced need for U.S. Military protection put the two nations on a collision course? In this timely collection of original essays, sponsored by the American Assembly, some of America's leading Asian experts offer answers to these important questions. The contributors' examination of U.S.-Japan relations fills an important need by paying special attention to the broader context of change in the Asia-Pacific region.